MEDIA KONSULTASI PENYAKIT KULIT PADA BALITA MENGGUNAKAN METODE CERTAINTY FACTOR - Utari, Sudi; Yudatama, Uky; Pujiarto, Bambang (Universitas Muhammadiyah Magelang, 2019)
The skin, which is the largest part  of the human body, is the body's first defense against bacterial and virus attacks. When the skin is exposed to the sun, dry weather, or bacteria, the reaction will spread to other parts of the body, and can even result in death if it is too late to be handled especially if the sufferers are children who are very vulnerable to disease. In this study an expert system was implemented to diagnose skin diseases in infants using the certainty factor method. certainty factor method is very suitable for expert systems that diagnose something that is uncertain. This system makes a diagnosis based on the symptoms felt by the user and then calculates certainty factors based on existing symptoms. Based on the test results by making comparisons between manual calculations and the one carried out by the system it is known that 90.22% of the diagnosis results get the same results so that the system is said to be suitable for use.